Red Cell Distribution Width as a Prognostic Indicator in Pediatric Heart Disease and after Surgery - Polat, Vural (Hindawi Publishing Corporation, 2014)
Background. Red cell distribution width (RDW) is an important marker which reflects inflammatory activity in many chronic diseases. The objective of this study is to investigate the impact of RDW on morbidity and mortality before and after pediatric congenital heart surgery. Methods. 107 patients with congenital heart disease, cardiac case group, and 70 patients, control group, without heart disease were retrospectively analyzed. Pre-, and postoperative and at discharge RDW of the cardiac patients were determined. Lengths of hospital and intensive care unit (ICU) stay and exited patients were determined. Results. Mean lengths of ICU and hospital stay were 3.3 ± 2.7 and 7.3 ± 2.9 days. In control group, mean preoperative RDW was 12.6 ± 1.4, while in cardiac case group it was significantly higher (15.1 ± 3.5). In cardiac case group, postoperative RDW were significantly higher than preoperative period, while RDW at discharge were significantly lower than postoperative estimates. A significant and a positive correlation was detected between lengths of ICU and hospital stay and RDW. RDW of the exited patients were significantly higher than the survivors. Conclusions. This study demonstrates that RDW can be used as an important indicator in the prediction of morbidity and mortality during pre-, and postoperative period of the pediatric congenital heart disease surgery.